Reducing warp and checking in 4 by 4 beams from small-diameter tropical species (tectona grandis, gmelina arborea, and cordia alliodora) obtained by turning the pith inside out. - Serrano-Montero, Rafael; Moya-Roque, Róger (Forest Products Society, 2015)
Small-diameter logs from plantation trees are prone to warp and to produce checks due to the presence of juvenile wood, growth stresses, and asymmetric shrinkage during the drying process. In the present study, we analyzed the possibility of producing sawn timber beams by using the inside-out (ISO) process. The material for the sawn timber beams was obtained from small-diameter logs of three tropical species planted in Costa Rica (Gmelina arborea, Tectona grandis, and Cordia alliodora). Changes in warp (crook and twist), checks (quantity, length, and depth), flexural and shear resistance, and glue line delamination were evaluated. We found that it was possible to produce beams from small-diameter logs of fast-growing plantations. This was achieved by turning the pith inside out and then gluing the green pieces. The ISO beams showed less warp and checking compared with solid wood. The modulus of rupture in the flexural test was not affected; however, the modulus of elasticity decreased. In the case of the glue line's shear resistance, the performance of G. arborea and C. alliodora were similar to that of solid wood, but T. grandis presented adherence problems, which caused low values of shear resistance. © Forest Products Society 2015.
Keywords: Árboles maderables; Gomas; Plantanciones; Ecosistemas tropicales; Madera; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry